2017
DOI: 10.1111/pan.13225
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use disorder and misuse: A review of the epidemiology and medical implications for pediatric anesthesiologists

Abstract: This educational review presents an overview of opioid use disorder, misuse and overdose among adolescents, and the clinical implications for anesthesiologists. It provides definitions, discusses the epidemiology worldwide, (focusing on North America), and emphasizes the clinical implications of patients with chronic opioid exposure, including perioperative pain management, as well as opioid overdose and prolonged use of opioids after acute exposure. In the USA, opioid use disorder and negative outcomes relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Examination of trends in opioid analgesic abuse from 2002 to 2011 showed that approximately 75% of US heroin users reported being introduced to opioids through prescription drug use [71,72]. However, despite evidence that misuse of prescription pain relievers has declined (from 4.7% in 2015 to 3.5% in 2019), heroin use has remained relatively stable over the past decade.…”
Section: Epidemiological Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of trends in opioid analgesic abuse from 2002 to 2011 showed that approximately 75% of US heroin users reported being introduced to opioids through prescription drug use [71,72]. However, despite evidence that misuse of prescription pain relievers has declined (from 4.7% in 2015 to 3.5% in 2019), heroin use has remained relatively stable over the past decade.…”
Section: Epidemiological Findingsmentioning
confidence: 99%
“…Findings of twin studies suggest that genetic variance explains approximately half of the liability for OUD, although some of this variance is likely a genetic disposition to drug use disorders in general [77][78][79]. However, environmental factors also play a prominent role, including drug availability, peer pressure, other substance use, adverse childhood experiences, family history of alcohol and drug use disorder, and other comorbid mental health problems [71,73,[80][81][82][83][84]. Predictors of prolonged opioid use in patients with musculoskeletal problems include past or current substance use problems, higher initially prescribed doses, mood disorders, and depression [71,85,86].…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Opioid analgesics are one of the most common treatments for pain. 3 With deaths from opioid misuse up 400% since 1999, 4 almost half a million adolescents in the United States using opioids nonmedically, 5 and poisoning deaths from prescription drug use among teens aged [15][16][17][18][19] increasing from 30% of all poisoning deaths in 2000 to 57% of all poisoning deaths in 2009, 6 nonpharmacologic pain management strategies are urgently needed, particularly for children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…While there are currently no uniform definitions related to describing opioid use and problematic opioid use, it is important to use consistent terminology throughout studies. Presented here are the ones currently recommended by the CDC, and found in several recent excellent guidelines and reviews on problematic opioid use 11,[14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%